An Investigation into Relationships between Classroom Acoustic Measurements and Voice Parameters of Teachers. Issue 3 (December 2015) - Durup, Nick; Shield, Bridget; Dance, Stephen; Sullivan, Rory
School teachers appear to have a greater prevalence of voice problems than the general population, yet classrooms are not designed with the safe use of teachers' voices in mind. In an effort to better understand the influence of classroom acoustic design on teachers' voice parameters measurements of teachers' voices in different classroom types have been made. An Ambulatory Phonation Monitor (APM) has been used to measure voice parameters (including the average voice sound pressure level, fundamental frequency and phonation time) directly from the skin vibrations in the neck, thus eliminating the effects of other noise sources in the environment. The rooms involved were acoustically benchmarked individually to enable relationships between the voice data and acoustic parameters, such as unoccupied ambient noise levels and reverberation times, to be investigated. The study data shows a positive correlation between unoccupied ambient noise levels and the average voice levels of the teachers, as well as between voice level and phonation time. There was no significant correlation in the study data between classroom reverberation times and voice levels or between voice level and fundamental frequency.